Coverage, compliance, acceptability and feasibility of a program to prevent pre-eclampsia and eclampsia through calcium supplementation for pregnant women: an operations research study in one district of Nepal. Issue 1 (December 2016) - Thapa, Kusum; Sanghvi, Harshad; Rawlins, Barbara; Karki, Yagya; Regmi, Kiran; Aryal, Shilu; Aryal, Yeshoda; Murakami, Peter; Bhattarai, Jona; Suhowatsky, Stephanie
Abstract Background Calcium supplementation during pregnancy has been shown to reduce the incidence of pre-eclampsia/eclampsia among women with low calcium intake. Universal free calcium supplementation through government antenatal care (ANC) services was piloted in the Dailekh district of Nepal. Coverage, compliance, acceptability and feasibility of the intervention were evaluated. Methods Antenatal care providers were trained to distribute and counsel pregnant women about calcium use, and female community health volunteers (FCHVs) were trained to reinforce calcium-related messages. A post-intervention cluster household survey was conducted among women who had given birth in the last six months. Secondary data analysis was performed using monitoring data from health facilities and FCHVs. Results One Thousand Two hundred-forty postpartum women were interviewed. Most (94.6 %) had attended at least one ANC visit; the median gestational age at first ANC visit was 4 months. All who attended ANC were counseled about calcium and received calcium tablets to take daily until delivery.79.5 % of the women reported consuming the entire quantity of calcium they received. The full course of calcium (300 tablets for 150 days) was provided to 82.3 % of the women. Consumption of the full course of calcium was reported by 67.3 % of all calcium recipients. Significant predictors of completing a full course were gestational age at first ANC visit and number of ANC visits during their most recent pregnancy (p  < 0.01). Nearly all (99.2 %) reported taking the calcium as instructed with respect to dose, timing and frequency. Among women who received both calcium and iron (n  = 1, 157), 98.0 % reported taking them at different times of the day, as instructed. Over 97 % reported willingness to recommend calcium to others, and said they would like to use it during a subsequent pregnancy. There were no stock-outs of calcium. Conclusions Calcium distribution through ANC was feasible and effective, achieving 94.6 % calcium coverage of pregnant women in the district. Most women (over 80 %) attended ANC early enough in pregnancy to receive the full course of calcium supplements and benefit from the intervention. High coverage, compliance, acceptability among pregnant women and feasibility were reported, suggesting that this intervention can be scaled up in other areas of Nepal.